Balance Performance in Young Adults With Hearing Aids: How Can It Be Affected by the Visual Cognitive Task? - Orhan, Emre; Batuk, İsa Tuncay; Batuk, Merve Ozbal (Journal of Speech, Language & Hearing Research, 2024)
Objective: The aim of this study was to investigate the effect of a visual cognitive additional task on balance performance in young adults with hearing aids (HAs). Method: Twenty young adult HA users and 20 controls were recruited for the study. Participants were asked to stand on a force plate using computerized dynamic posturography and perform a Sensory Organization Test (SOT) as a balance task under single-task (ST) and dual-task (DT) conditions. The DT condition involved performing a visual cognitive task (Backward Digit Recall) while maintaining balance. Balance performance was measured using equilibrium scores under four different conditions. Results: The results showed that SOT scores of HA users decreased significantly in the DT compared to the ST (p of Condition 1: < .001; p of Condition 4: < .001; p of Condition 6: = .001). HA users' SOT scores in the DT condition were statistically significantly lower than controls (p of Condition 1: < .003; p of Condition 4: < .009; p of Condition 6: = .004). This suggests that the presence of a visual cognitive additional task has a negative impact on balance performance in young adults with HAs. Conclusions: These findings highlight the importance of considering the impact of cognitive tasks on balance performance in young adults with HAs. Further studies should investigate the specific needs of hearing loss patients in multitasking conditions, including age, degree of hearing loss, and cognitive ability, to develop effective interventions to reduce the risk of falls.